PENGARUH KEPEMIMPINAN TERHADAP KINERJA CLEANING SERVICE DI PUSKESMAS MAMPANG PRAPATAN - Aceng Muchtarudin; Fuad Gagarin Siregar; Tuti Herawati; Farhat Abas (Journal Of Applied Multidisiplinary Studies, 2025)
This research is entitled "The Influence of Leadership on Cleaning Service Performance at the Mampang Prapatan Community Health Center". This study aims to examine the influence of leadership on the performance of cleaning services at the Mampang Prapatan Community Health Center. The sample taken in this research was 33 people. Data was collected using a questionnaire and then the data that had been collected was analyzed using the SPSS application program. In this research, the SPPS program used is version 25. The variables used are 2 variables. Dependent variable: leadership and Independent Variable: performance of cleaning service officers. The research results indicate that leadership (X) has a significant effect on the performance (Y) of officers working at the Mampang Prapatan Community Health Center. Leadership has a positive and significant effect on performance, namely 0.673 or 67.3%. Thus, the higher/better the leadership, the performance of the cleaners will increase, and conversely, the more leadership they follow, the performance will decrease.